MENGONSTRUKSI MODEL EVOLUSI PEMIKIRAN AKUNTANSI MAINSTREAM, INTERPRETIVE, DAN CRITICAL MELALUI SINTESIS LITERATUR METODOLOGIS - Ryketeng, Masdar; Nashiruddin Mushoddiq Rahman, Ahmad (ISAFIR: Islamic Accounting and Finance Review, 2025)
This study aims to construct a model of the evolution of accounting thought through a methodological literature synthesis addressing the paradigms of mainstream accounting, interpretive accounting, and critical accounting. The study employs a qualitative approach using a non-systematic literature review (non-SLR) method involving 24 articles and scholarly works relevant to the development of ontology, epistemology, methodology, and axiology in accounting research. Data were collected through the identification, selection, in-depth reading, information extraction, and classification of literature based on paradigmatic characteristics. The analysis was conducted using thematic literature synthesis to identify patterns of development, inter-paradigmatic relationships, and the dynamics of change in accounting thought. The findings indicate that the development of accounting thought has evolved through four major stages: mainstream accounting grounded in objectivism and positivism; interpretive accounting oriented toward social constructionism; critical accounting emphasizing emancipation and critique of power relations; and recent developments toward ecological and existential perspectives. The findings also show that the relationships among paradigms are not characterized by mutual replacement, but rather evolve through processes of critique, dialogue, and transformation, which generate methodological pluralism in accounting research. This study produces a conceptual model of the evolution of accounting thought that explains the philosophical shift in accounting knowledge from objectivism toward social constructionism, critical emancipation, and ecological consciousness. The model provides a more comprehensive understanding of paradigmatic development within the discipline of accounting.